2000
DOI: 10.1063/1.127084
|View full text |Cite
|
Sign up to set email alerts
|

Time–temperature–transformation diagram and microstructures of bulk glass forming Pd40Cu30Ni10P20

Abstract: Isothermal crystallization studies were performed on the bulk glass forming alloy Pd 40 Cu 30 Ni 10 P 20 in the undercooled liquid region between the glass transition and liquidus temperature, resulting in a complete time-temperature-transformation ͑TTT͒ diagram for crystallization. The TTT diagram shows a typical ''C'' shape with the nose at 50 s and 680 K. Assuming steady state nucleation and a diffusion-controlled growth rate, the TTT diagram was successfully fit over the entire range of the measurement. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 17 publications
5
54
0
Order By: Relevance
“…Besides, the experimental measurements of critical cooling rate were mainly performed in milligram-scaled samples (in the order of 10∼100 mg [44][45][46] ). In smaller samples, it's easier to achieve homogeneous composition and remove impurities to avoid crystallization.…”
Section: Possible Size-dependent Critical Cooling Rate In Real Conmentioning
confidence: 99%
“…Besides, the experimental measurements of critical cooling rate were mainly performed in milligram-scaled samples (in the order of 10∼100 mg [44][45][46] ). In smaller samples, it's easier to achieve homogeneous composition and remove impurities to avoid crystallization.…”
Section: Possible Size-dependent Critical Cooling Rate In Real Conmentioning
confidence: 99%
“…For example, a cooling rate of merely 0.1 K/s is required to suppress crystallization, and to form a metallic glass sample with diameter up to 72 mm for the Pd 40 Cu 30 Ni 10 P 20 alloy. 3 Measurements of viscosity, 4 crystallization, 5 diffusion, 6 density, 7 thermal expansion, 8 electron transport, 9 structure, 10 and specific heat capacity, 11 have been performed on bulk Pd 40 Cu 30 Ni 10 P 20 glass. Recently, Wang et al, 12 performed ultrasonic measurements at ambient temperature for as-cast bulk Pd 39 Cu 30 Ni 10 P 21 glass and samples annealed at various temperatures for 1.5 h, and found that two different crystallization processes are likely to exist in the supercooled liquid region.…”
mentioning
confidence: 99%
“…The experimental values of T l , T g , and H F were taken from Refs. [13][14][15][16]. Note that the total probability presented in Fig.…”
Section: Applied Physics Letters 97 024102 ͑2010͒mentioning
confidence: 99%
“…13,15 Here we quote the t onset at only four arbitrary T iso 's for each glass, as shown in Table II in Ref. 18.…”
Section: ͑3͒mentioning
confidence: 99%